Design Smart Phone Application for E-Health System (ICE) Urban Cities Based on Open-source Software: Machine Learning Based Approach - Haroon, Muhammad; Zhifang, Liao; Hingoro, Sadam Hussain (Transactions on Engineering and Computing Sciences, 2024)
Industry, environment, communication technology and many things have been revolutionized with the invention of mobile phone. Various technologies have been invented for the transfer of data. Mobile phones are considered a big hit for the devices to be connected without physical wires. The health aware mobile application developed in Android has been proposed. A patient is given some of the authorities and features to be active in various situations and store much of the information which can be easily used in difficult situations. Various health applications are already available and many of the features are available and the proposed app uses accelerometer for the detection of number of steps walked every day and the energy consumed and others. Medical sciences are improving the way of living a healthier life with constant flow, but no one knows about the E-health diseases. We are here to save human life from tragic accident by an emergency application. The main goal ICEApp is to improve the quality of care, reduce wastage of time, reduce the stress in emergency, reduce health care cost and most importantly save many lives. Health care has always been a challenge for every other person. Nowadays the health sector is evolved, and it turns toe-health systems where electronic devices give proper care to humans. This study was conducted by using the operating system we get the data from the clouds. This data was analysis in the machine learning algorithms. In this research, we get 70% accuracy of the heart attack disease 30% of the general emergencies results we get the results through the analysis of the machine learning algorithms. The result of e-health emergency application is presented in such a way that can be used as an aid to reduce emergency incidents that may occur. Through this application, we get almost 100% results by providing it to a client that was satisfied with the one clicks emergency feature and easy to use navigation.